HIGH-LEVEL SOLUBLE EXPRESSION OF THE FUNCTIONAL PEPTIDE DERIVED FROM THE C-TERMINAL DOMAIN OF THE OCEAN CUCUMBER LYSOZYME AND ANALYSIS OF ITS ANTIMICROBIAL ACTIVITY - PROF.DUHAOG, F.G; PROF.ZANG, P.J. MOONG, PROF.DUHAOG. F.G; PROF. ZANG; P.J. MOONG (International Journal of Multidisciplinary Research and Studies, 2021)
The sea cucumber lysozyme belongs to the family of invertebrate lysozymes and is believed to be a key defense considering protecting aquaculture animals against bacterial infection. Recently, evidence was found that the ocean cucumber lysozyme exerts broad-spectrum antimicrobial action in vitro against Gram-negative and Gram-positive bacteria, and it also has less attackable antimicrobial activity independent of its enzymatic activity. To explore the antimicrobial role of this non-enzymatic lysozyme and model its structure to novel antimicrobial peptides, the peptide from the C-terminal aminoalkanoic acid residues 70–146 of the ocean cucumber lysozyme in Stichopus japonicus (SjLys-C) was heterologously expressed in Escherichia coli Rosetta(DE3)pLysS.